Shi Zhengyi on Basic Theoretical Issues of Ethnologic Economics - Tian, Robert Guang (Advances in Social Sciences Research Journal, 2022)
This paper aims to introduce Professor Shi Zhengyi’s early theoretical views and contributions to ethnic economics to the international academic community. China’s ethnic minorities live in the western regions, and their economic and social development for a long time has been far behind that of the eastern and central areas where the Han majority live. Professor Shi Zhengyi proposed in March 1979 that China needed to establish and develop ethnologic economics. It is a particular branch of economics in China with solid Chinese characteristics. Ethnologic economics, starting from the status and role of ethnic factors in economic activities, studies the economic changes and economic relations of ethnic groups or ethnic regions. The ethnologic economy has the characteristics of duality and diversity, which is the starting point of the study of national economics. Ethnologic economics has adapted to the national conditions of China’s multi-ethnic country and the needs of China’s modernization drive. It has the dual disciplinary attribution of Ethnology and economics. It is hoped that the international academic community will take an interest in ethnologic economics and apply the research results of Chinese ethnologic economists to promote societies in other countries similar to China’s ethnic minority areas’ economic development.